HUBUNGAN ANEMIA PADA IBU MELAHIRKAN DENGAN KEJADIAN KETUBAN PECAH DINI - Utami, Risqi; Elytasari, Elytasari (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Premature rupture of membranes is the biggest cause of premature labor. and is an event in high-risk pregnancies, premature rupture of membranes (PROM) is a rupture of the membranes before birth or before signs of labor, this is caused by several predisposing factors, one of which is anemia. The purpose of this study was to determine the relationship between anemia and the incidence of premature rupture of membranes. This study uses a quantitative method with a cross sectional approach, with a population of 630 people, and sampling using purposive sampling with a total of 52 respondents. Based on the results of the research carried out, the results of the distribution of anemia frequency were obtained, in mothers who suffered from anemia (Hb levels <11gr%) were more than 30 people (57.69%), while in mothers who did not suffer from anemia (Hb levels> 11gr). %) was less, as many as 22 people (42.31%). The results of the Chi-Square statistical test obtained a p value of 0.010 < significance level (0.05), then H0 was rejected, so there was a relationship between anemia and the incidence of Premature Rupture of Membranes. Suggestions in this study are expected to provide correct knowledge and information about anemia and premature rupture of membranes to respondents so that respondents can pay attention to nutrition in subsequent pregnancies